Función de la intertextualidad bíblica en el Retrato de la Lozana Andaluza de Francisco Delicado - Jéromine François (Celestinesca, 2021)
La Lozana andaluza describes the story of a gifted prostitute. Whose adventures occur in Rome before the Sack of 1527. The writer, an Andalusian priest, fills his text with biblical references. As the purpose of his Retrato gives rise to debate and is valued according to its inappropriateness to the Christian doctrine, we study the role of the biblical intertextuality in the determination of this purpose. Indeed, the biblical hypotext presents here its traditional function as an auctoritas but it also constitutes a favored tool of linguistic games, a source of comic effects, and supplies the framework of the Retrato. Consequently, we highlight first some evidences that make an orthodox interpretation possible, and later some dissident tendencies that cross the story.